Learning communities: cultural project of the information society - Estefanía Fernández Antón (ADIDE Federación, 2014)
This article focuses on Learning Communities, social and cultural project that tries that all people have the same opportunities in contemporary society or information society. To this purpose, project tries to overcome social inequalities that suffer by people with less academic knowledge. We also provide information that allows this project is in schools of all stages. These data are the phases (sensitization, decision-making, phase of the dream, priority selection phase, planning phase, research, formation and evaluation) and implantation principles (dialogic seven principles, community participation, community formation and positive expectations).